THE EPIDEMIOLOGICAL ASPECTS OF CARIES SPREADING AND THE PECULIARITY OF DEVELOPMENT OF CARIOGENIC SITUATION IN THE CHILDREN WITH BRONCHIAL ASTHMA - O.V. Vozniy; T.Ye. Shumna; Ye.S. Lepetchenko (Український стоматологічний альманах)
Tooth decay is the most important early age children problem of the health of the oral cavity. It is medical and social problem of many developed countries and countries with transitional economy.